Comparative Study of DNA Extraction Methods for Halal Food Testing: Advantages, Disadvantages, and Recommended Methods - Citra Yulia Sari; Raditya Yudhi Pamungkasa; Setiyo Gunawan (Halal Research, 2025)
Identification of the halal status of food is a crucial aspect of the food industry, particularly in countries with a majority Muslim population. DNA extraction methods play a critical role in ensuring the halal status of food products by accurately detecting nonhalal substances. This study conducted a comparative evaluation of various DNA extraction methods used in halal food testing. We reviewed several DNA extraction methods listed in RSNI3 ISO 21571:2005 titled "Analytical Methods for the Detection of Genetically Engineered Products and Their Derivatives—Nucleic Acid Extraction". In RSNI3 ISO 21571:2005, five DNA extraction methods are discussed: the phenol-chloroform method, the silica method, the CTAB method, the polyvinylpyrrolidone (PVP) method, and the guanidine chloroform method. This study analyzes the advantages and disadvantages of the literature review. Additionally, we conducted an economic and process effectiveness review to identify the best method. Based on this analysis, we recommend the most suitable method for testing the halal status of various types of food sample. The results of this study are expected to serve as a guideline for testing laboratories and the food industry in selecting the optimal DNA extraction method for ensuring efficient and accurate halal status of products.